The metaphysics of historical Jesus research: an argument for increasing the plurality of metaphysical frameworks within historical Jesus research - Rowlands, Jonathan (2020)
In this thesis I examine the metaphysical presuppositions that influence modern academic historical Jesus research. I observe within the discipline a tendency to operate with the secular metaphysical presupposition to refuse to allow religious metaphysical presuppositions the opportunity to contribute to academic historiography, a tendency conceptualised in relation to the category of worldview (or Weltanschauung) as developed in the western philosophical tradition.